Real‐world outcomes for neoadjuvant capecitabine versus infusional 5‐fluorouracil in the treatment of locally advanced rectal cancer. Issue 8 (22nd August 2021) - Loft, Matthew; Wong, Hui‐Li; Kosmider, Suzanne; Lee, Margaret; Tie, Jeanne; Wong, Rachel; Jones, Ian T.; Croxford, Matthew; Steel, Malcolm; Faragher, Ian; Guerrieri, Mario; Christie, Michael; et al.
Abstract: Background: Neoadjuvant chemoradiation therapy is standard‐of‐care treatment for locally advanced rectal cancer (LARC). A pathological complete response (pCR) following chemoradiation therapy is an early indicator of treatment benefit and associated with excellent survival outcomes, with capecitabine largely replacing infusional 5‐fluorouracil as the choice in routine care of LARC. Aims: To analyse the uptake of capecitabine usage over time, and on the back of clinical trial data demonstrating equivalence between fluoropyrimidines, confirm that efficacy is maintained in the real‐world setting. Methods: We analysed data from a prospectively maintained colorectal cancer database at three Australian hospitals including patients diagnosed from January 2009 to December 2018. Pathological response was determined as either complete or incomplete and compared for patients receiving 5‐FU or capecitabine. Results: A total of 657 patients was analysed, 498 receiving infusional 5‐FU and 159 capecitabine. Capecitabine use has markedly increased from approval in 2014 in Australia, now being used in more than 80% of patients. Patient characteristics were similar by treatment, including age, tumour location and pre‐treatment stage. pCR was reported in 22/159 (13.8%) of capecitabine‐treated patients and 118/380 (23.7%) that received 5‐FU ( P  ≤ 0.01). More capecitabine‐treated patients received post‐operative oxaliplatin (44.2% vs 6.3%, P < 0.01). Two‐year progression‐free survival was similar (84.9% vs 88.0%, P = 0.34). Conclusions: Capecitabine is now the dominantly used neoadjuvant chemotherapy in LARC. Capecitabine use was associated with a lower rate of pCR versus infusional 5‐FU, a difference not explained by examined patient or tumour characteristics. Poor treatment compliance with oral therapy in the real‐world setting is one possible explanation.